Phenotypic heterogeneity unveils a negative correlation between antibiotic resistance and quorum sensing in Pseudomonas aeruginosa clinical isolates - Yang, Xiting; Zeng, Qianglin; Gou, Shiyi; Wu, Yi; Ma, Xiaoling; Zou, Hang; Zhao, Kelei (Frontiers in Microbiology, 2024)
Colonization of Pseudomonas aeruginosa in the lung environments frequently leads to the enrichment of strains displaying enhanced antibiotic resistance and reduced production of quorum-sensing (QS) controlled products. However, the relationship between the emergence of QS deficient variants and antibiotic resistance remains less understood. In this study, 67 P. aeruginosa strains were isolated from the lungs of 14 patients with chronic obstructive pulmonary disease, followed by determining their genetic relationship, QS-related phenotypes and resistance to commonly used antibiotics. The integrity of P. aeruginosa QS system was checked by DNA sequencing. The relationship between the QS system and antibiotic resistance was then assessed by correlation analyses. The function of the LasR protein and bacterial virulence were evaluated through homology modeling and nematode-infection assay. The influence of antibiotic on the development of extracellular protease production ability of P. aeruginosa was tested by an evolutionary experiment. The results showed that P. aeruginosa clinical strains displayed abundant diversity in phenotype and genotype. The production of extracellular proteases was significantly negatively correlated with antibiotic resistance. The strains with enhanced antibiotic resistance also showed a notable overlap with the mutation of lasR gene, which is the core regulatory gene of P. aeruginosa QS system. Molecular docking and Caenorhabditis elegans infection assays further suggested that P. aeruginosa with impaired LasR protein could also have varying pathogenicity. Moreover, in vitro evolution experiments demonstrated that antibiotic-mediated selective pressure, particularly from Levofloxacin contributed to the emergence of extracellular protease-negative strains. Therefore, this study provides evidence for the connection of P. aeruginosa QS system and antibiotic resistance, and holds significance for developing targeted strategies to address antibiotic resistance and improving the management of antibiotic-resistant infections in chronic respiratory diseases.